ESG no Brasil: da definição à implementação - uma análise do impacto e aplicabilidade na sustentabilidade empresarial e na indústria de alimentos - Prado, Vitória Cristina Peres do (Universidade Federal de São Carlos, 2024)
The concept of ESG (Environmental, Social and Governance) is increasingly proving to be a practical necessity for Brazilian companies. In the context of growing sustainability concerns amid finite natural resources and socio-environmental crises, effective management of ESG issues has become essential for corporate sustainability and market competitiveness. We demonstrate how ESG practices, particularly in the food industry, can mitigate environmental impacts, promote sustainable agriculture, and ensure safe and healthy production. Companies such as Citrosuco illustrate how the application of ESG practices can reduce deforestation, pollution, and soil degradation, while also strengthening corporate reputation and accessing new markets. Thus, the implementation of effective ESG practices is no longer optional but a vital necessity for companies aiming to promote corporate sustainability and maintain market relevance. Investments in education, training, and clear policies to ensure ongoing transparency and accountability are also crucial. In conclusion, the continuous evolution of ESG practices is essential for the survival and prosperity of Brazilian companies in a global scenario increasingly focused on sustainability.
ESG in Brasil
Keywords: ESG; Sustentabilidade; Indústria de alimentos; Impacto ambiental; Práticas empresariais; Desenvolvimento sustentável; Sustainability; Food industry; Environmental impact; Business practices; Sustainable development; CIENCIAS EXATAS E DA TERRA::QUIMICA